Pengaruh Kompetensi, Motivasi dan Locus of Control Terhadap Kinerja Karyawan dengan Etika Kerja Islam sebagai Variabel Moderating - Nunung Rifa’atul Mahmudah; Rinda Asytuti (LPMP Imperium, 2021)
This study aims to prove the effect of competence, motivation, and locus of control on employee performance with Islamic work ethics as a moderating variable on the Employees of the KoperasiLKMS BTM Pemalang. This study uses quantitative methods. Data collection by distributing questionnaires distributed to 55 employees as research samples. Data were analyzed using Partial Test, Simultaneous Test, and multiple regression analysis with MRA (Moderated Regression Analysis). The results showed that competence and locus of control) had a positive and significant influence on Employee Performance. At the same time, the motivation has a positive but not significant effect on employee performance either Partially or Simultaneously—the variable of Islamic work ethic moderates the variables of competence, motivation, and locus of control.